A longitudinal study of near-miss and maternal mortality at a tertiary centre in rural Uttarakhand: addressing the fourth delay - Mangla, Mishu; Nautiyal, Ruchira; ., Deepmala (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: India is a signatory of the sustainable development goals and is committed to reduce the maternal mortality ratio to less than 70 per lakh live births. Review of maternal deaths and near miss cases is a very important step towards achieving this aim. Methods: A prospective observational study was carried out in a tertiary care centre in rural Uttarakhand for a period of one and half year using WHO criteria for maternal near-miss, in an attempt to assess the quality of obstetric care in the region and to identify the possible delays leading to this. Results: Haemorrhage was the most common cause leading to severe maternal outcome, followed by early pregnancy complications and hypertensive disorders of pregnancy. The mortality index was 15% and maternal near miss to mortality ratio was 7:1. We could identify some type of delay in at least 70% of near miss and mortality cases. Although delay in seeking healthcare was the most common, lack of community participation was identified as an important fourth delay. Conclusions: For substantive reduction of maternal mortality in this region of Uttarakhand, the main action needed is strengthening of primary health care, educating the patients regarding warning signs of pregnancy and strengthening the social status of women in society, increasing community support in women health care.